Somnambulism (Sleepwalk): All We Want To Know - SAHA RAJSEKHAR, (International Journal of Pharma and Bio Sciences, 2012)
The objective of the article is too aware the medical professional and general mass regarding the sleep disorder known as sleepwalk. It’s a sincere effort to bring forward all the aspect weather quoted or forgotten in past. In the above article we have dealt with the cause of sleepwalk, its etiology, treatments, preventions. The article consists of various factors such as drugs and physiological causes responsible for the above disorder. The above disorder is simply characterized via an assessment that the patients exhibit activities like walking, or doing other physical activities as like but remaining in sleep. The above disorder is mostly seen in children and the count of it in adult is half. The basic point of concern with the person related with above disorder is he/she must not be engaged in any physical and social damage in the above state.